A case of acute abdomen-ruptured ovarian cysts - Gundluri, Poojashree; Gopalan, Ushadevi; Ravi, Sowmiya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Ovarian cyst rupture can lead to a spectrum of clinical presentations, from mild symptoms to life-threatening emergencies. This case report discusses a 26-year-old female who presented with lower abdominal distension and intermittent pain after a spontaneous incomplete abortion. Initial ultrasound revealed a large right adnexal cyst managed conservatively. During hospitalization, the patient developed acute abdominal pain with hypotension and tachycardia, prompting emergency laparotomy. Intraoperatively, a ruptured ovarian cyst with hemoperitoneum was identified and managed surgically. The case underscores the need for prompt differentiation between ovarian torsion and cyst rupture and highlights the role of surgical intervention in severe cases.